Value of contrast-enhanced ultrasonography in radiofrequency ablation of secondary hyperparathyroidism - Xiachuan Qin; Baofu Wang; Boliang Li; Changwei Lin; Xuebin Liu; Xisheng Xie (Renal Failure, 2021)
Objectives The purpose of the current study was to determine the performance of contrast-enhanced ultrasound (CEUS) in the assessment of radiofrequency ablation (RFA) of hyperplastic parathyroid glands due to secondary hyperparathyroidism (SHPT). Methods Thirty-two patients, each with ≥4 hyperplastic parathyroid glands due to SHPT, underwent RFA via hydro-dissection. CEUS was performed in each patient before and during RFA. The patients in whom the intact parathyroid hormone (iPTH) level did not decrease to 300 pg/ml were examined by CEUS. The iPTH, serum calcium, and serum phosphorus levels before and after RFA were compared. Results Ablation was achieved in all patients (131 ablated glands). The volume of the glands was 479.88 ± 549.3mm3. The pre-operative and day 1 post-operative iPTH levels were 2355 ± 1062 and 292.7 ± 306.8 pg/ml, respectively. Three nodules in three patients showed little enhancement on CEUS on post-operative day 1. The iPTH level was <300 pg/mL on post-operative day 1 in 23 patients, which indicated complete ablation; follow-up evaluations were therefore performed. The pre- and post-operative iPTH levels in the 23 patients were 2113 ± 787.2 and 106.2 ± 84.62 pg/ml, respectively (p < 0.05), and the 6- and 12-month post-operative iPTH levels were 111.1 ± 56.57 and 117.6 ± 97.08 pg/ml, respectively (p > 0.05). Conclusions CEUS-guided RFA is effective and feasible for the treatment of ≥4 hyperplastic parathyroid glands. CEUS was shown to assist the surgeon before, during, and after RFA. CEUS on post-operative day 2, but not immediately post-operatively, was shown to accurately reflect gland perfusion.